Growth and Hope after loss: How TAPS facilitates posttraumatic growth in those grieving military deaths - Moore, Melinda; Palmer, Jerry K.; Cerel, Julie; Ruocco, Kim (Frontiers in Psychology, 2022)
We examined posttraumatic growth for 691 participants of the Tragedy Assistance Program for Survivors (TAPS). Peer mentors of bereaved individuals experienced greater posttraumatic growth (PTG) and reported higher psychological health. Active involvement in TAPS and resilience consistently and positively predicted all types of PTG. These prediction models were far stronger (R2, AIC) for the suicide-bereaved sample and post-hoc analyses suggest suicide-bereaved benefitted more from active participation in TAPS.